Growth Performance, Nutritional Behaviour, and Faecal Consistency Score of Feedlot Nellore Brown Lambs Fed Diets with Probiotic and Sodium Bicarbonate - Harani, Maram; Yugandhar, Vannam; Sireesha, Elluru; Naik, Korra Balaji; Mallikarjun, Malavathu; Radhakumari , Chandra (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
A study was undertaken at IFS shed, KVK, Kalyandurg, (AP, India) to determine the effect of feeding probiotic and sodium bicarbonate on growth performance, nutritional behaviour, and faecal consistency score in Nellore brown lambs. Twenty four ram lambs were randomly assigned to three group on the basis of body weight, viz., T1 (control): Super napier, Hedge lucerne and Concentrate mixture with 20% protein, T2 (treatment): control feed with 15 g of probiotics, and T3 (treatment): control feed with 20 g sodium bicarbonate per kg DMI. The final body weights, average daily weight gain and feed conversion ratio were significantly higher in both the treatment groups than in the control group. The behaviour parameters like ingestion, rumination, chewing and idleness were also significantly higher in probiotic and sodium bicarbonate supplemented groups. However, the rumination time in min/day, was recorded to have negative linear association with feed additive supplemented groups. The faecal consistency scores for T1, T2 and T3 differed significantly among treatment groups, whereas normal faeces were recorded in probiotics supplemented groups.